Pancasila as a Container for Character Building - Ellen Rolinda; Prety Niken Mustofa; Tanaya Marlian Alfianti; Riska Andi Fitriono (CV. Rayyan Dwi Bharata, 2022)
Pancasila represents the good character of the Indonesian nation and is a very appropriate spirit if applied in Indonesia, a country with many cultural problems, and a complex government. Pancasila contains five very good rules used to build the character of the Indonesian nation. Pancasila is the basic ideology of the Indonesian nation, inherited from the ancestors of our founders. Pancasila consists of two Sanskrit words, panca which means five and sila which means principle or principle. Pancasila represents the character of the Indonesian nation and is a very appropriate spirit when applied in Indonesia, a country with many cultural problems, and complex governance. The life of the Indonesian nation demands the application of the values contained in Pancasila, which reflects the original personality of the Indonesian nation. The values, norms, and ethics contained in Pancasila become a very complete and unified part of the personality of every Indonesian citizen, as well as giving direction to the Indonesian nation. Furthermore, Pancasila also signifies character values that are incorporated into the lives of Indonesian citizens.